Formation rates of Subantarctic mode water and Antarctic intermediate water within the South Pacific - Hartin, CA; Fine, RA; Bernadette Sloyan; Talley, LD; Chereskin, TK; Happell, J (2011)
The formation of Subantarctic Mode Water (SAMW) and Antarctic Intermediate Water (AAIW) significantly contributes to the total uptake and storage of anthropogenic gases, such as CO 2 and chlorofluorocarbons (CFCs), within the world's oceans. SAMW and AAIW formation rates in the South Pacific are quantified based on CFC-12 inventories using hydrographic data from WOCE, CLIVAR, and data collected in the austral winter of 2005. This study documents the first wintertime observations of CFC-11 and CFC-12 saturations with respect to the 2005 atmosphere in the formation region of the southeast Pacific for SAMW and AAIW. SAMW is 94% and 95% saturated for CFC-11 and CFC-12, respectively, and AAIW is 60% saturated for both CFC-11 and CFC-12. SAMW is defined from the Subantarctic Front to the equator between potential densities 26.80-27.06kgm -3 , and AAIW is defined from the Polar Front to 20°N between potential densities 27.06-27.40kgm -3 . CFC-12 inventories are 16.0×10 6 moles for SAMW and 8.7×10 6 moles for AAIW, corresponding to formation rates of 7.3±2.1Sv for SAMW and 5.8±1.7Sv for AAIW circulating within the South Pacific. Inter-ocean transports of SAMW from the South Pacific to the South Atlantic are estimated to be 4.4±0.6Sv. Thus, the total formation of SAMW in the South Pacific is approximately 11.7±2.2Sv. These formation rates represent the average formation rates over the major period of CFC input, from 1970 to 2005. The CFC-12 inventory maps provide direct evidence for two areas of formation of SAMW, one in the southeast Pacific and one in the central Pacific. Furthermore, eddies in the central Pacific containing high CFC concentrations may contribute to SAMW and to a lesser extent AAIW formation. These CFC-derived rates provide a baseline with which to compare past and future formation rates of SAMW and AAIW.